Effects of foliar fungicide on yield, micronutrients, and cadmium in grains from historical and modern hard winter wheat genotypes. - Hollman Motta-Romero (Public Library of Science (PLoS), 2021)
Plant breeding and disease management practices have increased the grain yield of hard winter wheat (Triticum aestivum L.) adapted to the Great Plains of the United States during the last century. However, the effect of genetic gains for seed yield and the application of fungicide on the micronutrient and cadmium (Cd) concentration in wheat grains is still unclear. The objectives of this study were to evaluate the effects of fungicide application on the productivity and nutritional quality of wheat cultivars representing 80 years of plant breeding efforts. Field experiments were conducted over two crop years (2017 and 2018) with eighteen hard winter wheat genotypes released between 1933 and 2013 in the presence or absence of fungicide application. For each growing season, the treatments were arranged in a split-plot design with the fungicide levels (treated and untreated) as the whole plot treatments and the genotypes as split-plot treatments in triplicate. The effects on seed yield, grain protein concentration (GPC), micronutrients, phytic acid, and Cd in grains were measured. While the yield of wheat was found to increase at annualized rates of 26.5 and 13.0 kg ha-1 yr-1 in the presence and absence of fungicide (P < 0.001), respectively, GPC (-190 and -180 mg kg-1 yr-1, P < 0.001), Fe (-35.0 and -44.0 μg kg-1 yr-1, P < 0.05), and Zn (-68.0 and -57.0 μg kg-1 yr-1, P < 0.01) significantly decreased during the period studied. In contrast to the other mineral elements, grain Cd significantly increased over time (0.4 μg kg-1 yr-1, P < 0.01) in the absence of fungicide. The results from this study are of great concern, as many mineral elements essential for human nutrition have decreased over time while the toxic heavy metal, Cd, has increased, indicating modern wheats are becoming a better vector of dietary Cd.